The art of history : literary perspectives on Greek and Roman historiography - Liotsakis, Vasileios; Farrington, Scott (Trends in classics. Supplementary volumes, 2016)
A significant trend in the study of Greek and Roman historiographers is to accept that their works are to a degree both science and fiction. As scholarly interest broadens, in addition to evaluating ancient historians on the basis of the reliability of the information they record, and verifying the narratives against various elements of the material (inscriptions, excavations, numismatics), new studies are beginning to elaborate on the stylistic and narrative qualities of the texts themselves. The present volume offers a fine collection of essays that on the whole emphasize the literary dimensions of the ancient Greek and Roman historians. Offering narratological, linguistic, and theoretical approaches to historiography, the contributors of the book elaborate on the intersections between historiography and other literary genres, the literary manipulation of military events and the criteria of selectivity, the reception of ancient historical texts in other genres, time and space in historical narrative, and plenty of other relevant topics. The shared belief of the authors is that there is a close interrelation between the literary features and the scientific value of ancient Greek and Roman historiography.